Tinjauan Yuridis terhadap Keabsahan Perjanjian Pengikatan Jual Beli Pasca Kepailitan Developer - Annisa Nurul Fitri; Priestia Nuzdiana; Citra Amalia (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the legal robustness of the Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB) in property transactions, with particular emphasis on circumstances where the developer is declared bankrupt. Employing a normative legal research design, the study relies on secondary legal materials and qualitative analysis to assess applicable legal doctrines, statutory frameworks, and judicial principles governing PPJB. The analysis demonstrates that PPJB functions as a preliminary contractual instrument between developers and purchasers, typically concluded prior to project completion and frequently executed in notarial form to strengthen its evidentiary value. Two principal categories of PPJB are identified, namely fully paid and partially paid agreements. The findings indicate that a fully paid PPJB executed before a notary prior to the declaration of bankruptcy provides a strong legal position for buyers and enables the agreement to be excluded from the bankruptcy estate. In contrast, a partially paid PPJB, particularly one not formalized through a notarial deed and where the buyer has not yet obtained effective control over the property, offers limited legal protection and places the buyer in a weaker position within bankruptcy proceedings. This study contributes to the development of legal scholarship by clarifying the differential legal consequences of PPJB classifications in bankruptcy contexts and reinforcing the role of notarial instruments in enhancing contractual certainty. Practically, the findings provide guidance for purchasers, legal practitioners, and policymakers by emphasizing the importance of notarial execution and payment completion as preventive legal strategies to mitigate risks arising from developer insolvency.